PERAN PAKTA INTEGRITAS DALAM MEWUJUDKAN GOOD AND CLEAN GOVERNMENT - Afifah, Qoni'; Febry Bayu Listianto (Program Studi Hukum Tata Negara Islam, Fakultas Syariah, Universitas Islam Negeri (UIN) Datokarama Palu, 2024)
The dream of realizing good and clean government is a common narrative among all government administrators. To make these ideals come true so that they are not just a dream, of course, efforts are needed to achieve them. Indonesia, as a rule of law country, certainly has its own path or method in pursuing the ideals of good and clean government. Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform Number 49 of 2011 concerning General Guidelines for Integrity Pacts in Government/Institutional and Regional Government Environments is one of the strategies for realizing good and clean government. Research using this normative method examines the role of the integrity pact contained in the Minister of Administrative Regulations with the ideal of creating good and clean government as codified in Law Number 30 of 2014 and also various literature that is in line with the discussion. The harmony of the content of the text in the Regulation of the Minister for Empowerment of State Apparatus and Bureaucratic Reform Number 49 of 2011 with the principles of good and clean government has led researchers to conclude that this legal product has the potential to realize the ideals of government. That goal, it's just a matter of how to execute it. Abstrak Cita-cita terwujudnya good and clean government merupakan narasi yang sudah umum disemua penyelenggara pemerintahan. Terwujudnya cita-cita tersebut agar tidak hanya menjadi sebuah angan-angan tentu diperlukan adanya upaya dalam menggapainya. Indonesia sebagai negara hukum tentu memiliki jalur atau metodenya sendiri dalam mengupayakan cita-cita pemerintahan yang baik dan bersih tersebut. Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 49 Tahun 2011 tentang Pedoman Umum Pakta Integritas di lingkungan pemerintahan/lembaga dan pemerintahan daerah menjadi salah satu strategi demi terwujudnya pemerintahan yang baik dan bersih. Penelitian dengan metode normatif ini mengkaji peran pakta integritas yang ada di dalam Permenpan tersebut dengan cita-cita terciptanya pemerintahan yang baik dan bersih (good and clean government) sebagaimana telah terkodifikasi dalam Undang-Undang Nomor 30 Tahun 2014 dan juga berbagai literatur yang sejalur dengan pembahasan ini. Keselarasan isi teks dalam Peraturan Menteri Pendayagunaan Aparatur Negara dan Reformasi Birokrasi Nomor 49 Tahun 2011 dengan asas-asas pemerintahan yang baik dan bersih (good and clean government) menjadikan peneliti memiliki kesimpulan bahwa produk hukum yang satu ini berpotensi mewujudkan cita-cita tersebut, tinggal bagaimana eksekusinya.